Experimental and characterisation of eroded surfaces of T-glass fibre embedded in polyester matrix - Chowdhury, M. A.; Debnath, U. K.; Mia, M. S.; Nuruzzaman, D. M. (Inderscience Enterprises Ltd., 2017)
The versatile applications of composite materials in different concerned mechanical processes at different environmental conditions, the damage due to striking of solid particles on T-glass fibre reinforced polyester is analysed under this study. The non-uniform geometrical shaped silica sand (SiO2) particles (300–355 μm, 355–500 μm, and 500–600 μm) are selected as erodent. During test, impingement angles 15°–90°, impingement velocity 30–50 m/sec and standoff distance 15–25 mm at ambient temperature are considered. Results reveal that the maximum erosion of targeted composite is found at 60°impingement angle which indicates the semi-ductile characteristics of test sample. The eroded surfaces exhibit micro-cracking, micro-cutting, ploughing and pulverisation at 60° impingement angle. The average roughness 5, 50 and 100 μm is obtained for 30°, 60° and 90° impingement angles, respectively. The surface characterisation is done by SEM and 3D SEM analysis.